Breaking the Glass Ceiling? Female Participation in Militant Organizations in Islamic State Affiliates in Southeast Asia - Jadoon, Amira (Terrorism and political violence, 2022)
Prior research on female participation in militant organizations explores organizational and individual factors that influence women’s recruitment, and the roles women fulfill. However, most research focuses either on transnational organizations or local militant groups. Within this study, we explore how linkages with transnational groups shape female participation within their overseas affiliate organizations. We employ an original dataset of female militants arrested or killed between 2014 and 2019 in the Philippines, Malaysia, and Indonesia, accounting for organizational affiliation. Overall, we find that female participation in militant groups increased between 2015 and 2017, with most of the increase associated with the Islamic State. While most women with an Islamic State association assumed non-combat roles, more than a third assumed combatant roles, indicating the influence of country-level and regional dynamics. Based on our data, female combatants with an Islamic State association served exclusively as either suicide attackers or conducted bombings, diverging from the varied roles assumed by women combatants in other groups in the region. Overall, our findings highlight how the nature of transnational organizations can combine with the local dynamics of their affiliate groups to produce unique trends in the local female militant landscape.